Children and Young People’s Self-Reported Experiences of Asthma and Self-Management Nursing Strategies: An Integrative Review - Kemble, Hannah; Foster, Mandie; Blamires, Julie; Mowat, Rebecca (Elsevier, 2024)
Aim To explore children and young people's (CYP) (5–24 years of age) self-reported experiences of asthma self-management strategies (ASMS) with nursing involvement across various settings. Background Childhood asthma is an increasingly significant health issue, highlighting the importance of acquiring self-management skills to optimise future health outcomes. Registered nurses play a pivotal role in delivering appropriate, personalized self-management support. Methods This integrative review searched four electronic databases: Cumulated Index to Nursing and Allied Health Literature via Elton B. Stephens Company, Medical Literature Analysis and Retrieval System Online (MEDLINE), Object, View and Interactive Design (OVID), and PubMed, that followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis flowchart. Included studies were critically appraised using the Joanna Briggs Institute critical appraisal tools. Braun and Clarks thematic analysis was used to generate themes, and sub-themes. Findings Fifteen studies were included for review. Thematic analysis generated three themes being healthy literacy; health and wellbeing; and tools and working together. Conclusions Asthma continues to have negative physical, psychological, and social implications among CYP. CYP are both willing and capable of engaging in ASMS and learning self-management skills, however, continue to have unmet self-management needs.
Keywords: 1110 Nursing; 1114 Paediatrics and Reproductive Medicine; Nursing; 3213 Paediatrics; 4205 Nursing